2018
DOI: 10.1089/ars.2017.7086
|View full text |Cite
|
Sign up to set email alerts
|

Differential Impact of Flavonoids on Redox Modulation, Bioenergetics, and Cell Signaling in Normal and Tumor Cells: A Comprehensive Review

Abstract: Significance: Flavonoids can interact with multiple molecular targets to elicit their cellular effects, leading to changes in signal transduction, gene expression, and/or metabolism, which can, subsequently, affect the entire cell and organism. Immortalized cell lines, derived from tumors, are routinely employed as a surrogate for mechanistic studies, with the results extrapolated to tissues in vivo.Recent Advances: We review the activities of selected flavonoids on cultured tumor cells derived from various ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 285 publications
(320 reference statements)
0
28
0
Order By: Relevance
“…For a detailed review of anticancer activity reported over the last 5 yr consult Zhou et al. () and on mechanisms of action see Kerimi & Williamson ().…”
Section: Bioactivitymentioning
confidence: 99%
“…For a detailed review of anticancer activity reported over the last 5 yr consult Zhou et al. () and on mechanisms of action see Kerimi & Williamson ().…”
Section: Bioactivitymentioning
confidence: 99%
“…Quercetin safety has been critically reviewed (Harwood et al., ; Okamoto, ) and high‐purity quercetin was given Generally Recognized As Safe (GRAS) status in 2010 (FDA, ). Over the last few decades, many biological studies on quercetin have been published, reporting a wide range of biological effects in vitro and in vivo including anti‐inflammatory and neuroprotective activities (Boots, Haenen, & Bast, ; Dajas, ; Gibellini et al., ; Harwood et al., ; Kawabata, Mukai, & Ishisaka, ; Kerimi & Williamson, ; Okamoto, ; Russo, Spagnuolo, Tedesco, Bilotto, & Russo, ).…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are ubiquitous in plant-based food products, such as fruits, vegetables and tea extracts and in medicinal plants. Their anticancer activity has been attributed to the inhibition of DNA damage, the inhibition of cell cycle associated proteins, the induction of apoptosis, the modulation of cell signaling pathways involved in proliferation and in the inhibition of carcinogenic metabolite formation (George et al, 2017;Curti et al, 2017;Kerimi et al, 2017;Clementino et al, 2017). The hydroxylated flavonoids apigenin, luteolin, quercetin and kaempferol are the main constituents of various dietary products and beverages and have been the focus of extensive research over the 6 last years.…”
Section: Introductionmentioning
confidence: 99%